N-carbamylglutamate supplementation regulates hindgut microbiota composition and short-chain fatty acid contents in Charollais and Small Tail Han crossbred sheep - Ma, Wei; Yuan, Meiling; Chang, Shuai; Wang, Chunqiang (Frontiers in Veterinary Science, 2023)
Introduction The objective of this study was to investigate the effects of N-carbamylglutamate (NCG) supplementation on the growth performance, hindgut microbiota composition, and short-chain fatty acid (SCFA) contents in Charollais and Small Tail Han crossbred sheep. Methods A total of 16 female crossbred mutton sheep (Charollais × Small Tail Han), aged 4 months, with an initial body weight of 30.03 ± 0.08 kg, were utilized in a 60 days experiment. The sheep were divided into two groups based on their initial body weight. Each group consisted of 8 replicates, with each individual sheep considered as a replicate. The dietary treatments comprised a basal diet supplemented with either 0.00% or 0.12% NCG. Results and discussion Our findings indicate that NCG supplementation did not have a significant effect on the growth performance of mutton sheep. However, it did lead to changes in hindgut SCFA contents. Specifically, NCG supplementation increased the content of propanoic acid while decreasing acetic acid and hexanoic acid in the hindgut. Through microbiota analysis using the 16S rRNA technique, we identified Lachnospiraceae_NK3A20_group and Parasutterella as biomarkers for the hindgut microbiota in mutton sheep fed a diet containing NCG. Further analysis of the microbiota composition revealed that NCG supplementation significantly increased the abundance of Lachnospiraceae_NK3A20_group and Parasutterella, while decreasing unclassified_f_Lachnospiraceae and Lachnoclostridium. Correlation analysis between hindgut SCFA contents and microbiota composition revealed that the abundance of Lachnoclostridium was positively correlated with the contents of acetic acid and hexanoic acid, but negatively correlated with propanoic acid. Additionally, the abundance of Lachnospiraceae_NK3A20_group and Parasutterella was positively correlated with the content of propanoic acid, while being negatively correlated with acetic acid and hexanoic acid. Based on these findings, we conclude that dietary supplementation of 0.12% NCG can modulate hindgut SCFA contents in mutton sheep by regulating the composition of the hindgut microbiota.